2021
DOI: 10.1177/1179547621994573
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Management of Thyrotoxicosis Associated with Atrial Fibrillation and Heart Failure: Two Case Reports

Abstract: Background: Thyrotoxicosis is a clinical syndrome with high amounts of free thyroid hormone levels causing elevated thyroid hormone function in body tissues. Prolonged effects of free thyroid hormones may lead to cardiac complications such as atrial fibrillation (AF) and heart failure (HF). Case 1: A 31-year-old female, was admitted due to difficulty in breathing, generalised body swelling and jaundice. She was dyspnoeic with an irregular heart rate, and presented with abnormal vitals, liver and thyroid functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…A study states that thyrotoxicosis causes catastrophic cardiac complications that are difficult to manage, such as atrial fibrillation and heart failure, so preoperative optimization of thyrotoxic patients is required to reduce this problem (3a) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study states that thyrotoxicosis causes catastrophic cardiac complications that are difficult to manage, such as atrial fibrillation and heart failure, so preoperative optimization of thyrotoxic patients is required to reduce this problem (3a) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is prevalent in this setting, with frequent readmissions and poor outcomes. 9 , 10 Hypertension and type 2 diabetes mellitus were the most common comorbidities. This study emphasizes a shift in disease burden toward cardiovascular diseases as the leading cause of hospital admission and death.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that CVDs, including heart failure and stroke, were the most common causes of hospital admission, followed by chronic kidney disease and respiratory tract infections. Heart failure is prevalent in this setting, with frequent readmissions and poor outcomes 9,10 . Hypertension and type 2 diabetes mellitus were the most common comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Thyrotoxicosis is a common clinical syndrome that results from tissue exposure to excessive amounts of circulating thyroid hormones, irrespective of the source [1] , [2] . Determining the cause of thyrotoxicosis is essential for establishing appropriate management [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Thyrotoxicosis, with any cause, may affect many organ systems, including bone, skin, gastrointestinal, nervous, and cardiovascular systems (CVS). The CVS complications are the most common and life-threatening condition, causing hospitalization and death [1] , [4] . Atrial fibrillation (AF) is the type of arrhythmia and CVS complication most often found in patients with hyperthyroidism or thyrotoxicosis.…”
Section: Introductionmentioning
confidence: 99%